2020
DOI: 10.1109/jproc.2019.2932116
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Ultrasound Imaging

Abstract: Deep learning is taking an ever more prominent role in medical imaging. This paper discusses applications of this powerful approach in ultrasound imaging systems along with domain-specific opportunities and challenges.ABSTRACT | We consider deep learning strategies in ultrasound systems, from the front-end to advanced applications. Our goal is to provide the reader with a broad understanding of the possible impact of deep learning methodologies on many aspects of ultrasound imaging. In particular, we discuss m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 225 publications
(132 citation statements)
references
References 116 publications
(124 reference statements)
0
119
0
Order By: Relevance
“…Several attempts to use machine learning and deep learning for US-based disease diagnosis and characterisation have been reported [8]. For instance, super-resolution in US localisation microscopy and beamforming uses deep learning techniques for the removal of artefacts in element-wise complex in-phase and quadrature data [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to use machine learning and deep learning for US-based disease diagnosis and characterisation have been reported [8]. For instance, super-resolution in US localisation microscopy and beamforming uses deep learning techniques for the removal of artefacts in element-wise complex in-phase and quadrature data [9].…”
Section: Introductionmentioning
confidence: 99%
“…In their seminal work, Gregor and LeCun unfolded the Iterative Shrinkage-Thresholding Algorithm (ISTA) for sparse coding [20,21] into a learned ISTA (LISTA) network, and demonstrated that propagating the data through only 10 blocks is equivalent to running the iterative algorithm for 200 iterations, without requiring fine-tuning of any parameters. In recent years, the concept of algorithm unfolding has been applied to many different problems, including, among others, single-image-superresolution (deblurring) [22,23], image denoising and image inpainting [24], ultrasound localization microscopy [25], ultrasound clutter suppression [26], and multi-channel source separation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, automatic image analysis by machine and deep learning (DL) methods have already shown promise for reconstruction, classification, regression and segmentation of tissues using ultrasound images [16], [17]. In this paper we describe the use of DL to assist clinicians in detecting COVID-19 associated imaging patterns on point-of-care LUS.…”
mentioning
confidence: 99%